On the matter of classifying node connections - Armstrong, Colin (IEEE Computer Society, 2011)
Traditional network classification has focused on four aspects; structure, node, link, and dynamics. The purpose of this paper is to consider a node individually and to base classification on the types of links it possesses. A basic network provides only three possibilities with the `Mutual, Asynchronous, Null' MAN system providing for sixteen different combinations of link patterns. This paper introduces a concept to resolve an unsatisfactory situation and to determine the significance of a `null' link. The proposed extension of the MAN system provides thirty two different combinations of link patterns, and a system for acknowledging proportional combinations of node links, thereby facilitating a potentially more refined classification of node link pattern.